Study of life style determinants of overweight and obesity among school going adolescents in urban Jabalpur, Madhya Pradesh, India - Tomar, Shashi Prabha; Kasar, Pradeep Kumar; Tiwari, Rajesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Obesity has become a colossal epidemic causing serious public health concern and contributes to 2.6 million deaths worldwide every year. Indian data regarding current trends in childhood obesity are emerging. Considering the fact that India has rapidly growing middle class easily habituated for enormous lifestyle changes in recent decades responsible for developing potential platform for obesity among youths. Accordingly, the objective of the present study was to evaluate the associations between overweight, obesity and several lifestyle factors, including physical activity, sedentary behaviours among adolescents aged 10-17 years. Methods: A cross-sectional study was carried out in two schools of Jabalpur located around medical college area , 184 students effectively interviewed by predesigned questionnaire regarding Socio-demographic profile ie current residence, age, mothers educational and occupational status and family size and life style practices like the physical activity questions designed to asses typical time spent per day on games and outdoor activity, on sedentary activities, including television (TV) viewing, video games, and computer and internet use. Data entry and data processing were carried out using the SPSS version 17 software and data analyses were applied using the appropriate statistical tests of significance. Results: Prevalence of obesity and overweight: Of the 184 adolescents studied, 7.6% were obese and 2.2% were pre-obese. Conclusions: Among all of the lifestyle factors assessed, overweight and obesity exhibited associations with less frequent physical activity, and more television and internet use.